Nutritional muscular dystrophy in lambs reared on pasture in semiarid region of Brazil (Research, Society and Development, 2020)
This article presents important data on the diagnosis of nutritional muscular dystrophy (NMD) in sheep reared in the semiarid region of Northeast Brazil, with a focus on medical clinic data, nutritional management, anatomopathological aspects and quantification of serum selenium by highly sensitive analytical methodology. The semiarid region of Brazil is of great importance in the creation of small ruminants and many diseases that affect herds are related to failures in nutritional management, sanitary measures, periods of greater drought or low rainfall, little availability of native forage at certain times of the year and lack of supplementation with energy nutrients, proteins and minerals. The lack of publications on outbreaks of selenium deficiency demonstrates the importance of diagnosing in this area. The mean concentration of Se in the serum from the lambs was very low (2.52±1.02µg/L). The findings in the skeletal muscles are compatible with the characteristics observed in NMD, characterized by necrosis and calcification of myofibrils. In addition, necrotizing vasculitis in hepatic arterioles and hepatocellular coagulation necrosis in hepatocytes were observed, probably triggered by lipid peroxidation of cell membranes. The lambs from this outbreak, reared on pasture in the semiarid region, presented low serum Se concentration, with clinical and anatomopathological manifestation of NMD. Thus, supplementation with Se in the diet should be recommended regularly to avoid the appearance of new cases. Serum Se levels are useful indicators for the diagnosis of nutritional muscular dystrophy in lambs, associated with clinical and anatomopathological data.